2016
DOI: 10.1039/c6cp00012f
|View full text |Cite
|
Sign up to set email alerts
|

Amino-functionalized breath-figure cavities in polystyrene–alumina hybrid films: effect of particle concentration and dispersion

Abstract: We report the formation of breath-figure (BF) patterns with amino-functionalized cavities in a BF incompatible polystyrene (PS) by incorporating functionalized alumina nanoparticles. The particles were amphiphilic-modified and the modifier ratio was regulated to achieve a specific hydrophobic/hydrophilic balance of the particles. The influence of the physical and chemical properties of the particles like particle concentration, the hydrophobic/hydrophilic balance, etc., on particle dispersion in solvents havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Various experimental techniques were successfully applied for breath-figure self-assembly, including drop-casting [ 66 , 67 , 68 , 69 , 70 , 71 ], spin-coating [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ], the “doctor-blade” technique [ 79 , 80 ], and dip-coating [ 46 , 54 , 58 , 81 , 82 , 83 ]. When breath-figures-inspired patterns are formed under drop-casting, a drop of polymer solution is deposited by a precise micro-syringe (or micro-injector) on a solid substrate and exposed to air flow with a controlled humidity [ 66 , 67 , 68 , 69 , 70 , 71 ]. The spin-coating process involves putting a polymer solution on the center of the substrate, which is either spinning at low speed or not spinning at all.…”
Section: Processes Used For Breath-figure Self-assemblymentioning
confidence: 99%
“…Various experimental techniques were successfully applied for breath-figure self-assembly, including drop-casting [ 66 , 67 , 68 , 69 , 70 , 71 ], spin-coating [ 72 , 73 , 74 , 75 , 76 , 77 , 78 ], the “doctor-blade” technique [ 79 , 80 ], and dip-coating [ 46 , 54 , 58 , 81 , 82 , 83 ]. When breath-figures-inspired patterns are formed under drop-casting, a drop of polymer solution is deposited by a precise micro-syringe (or micro-injector) on a solid substrate and exposed to air flow with a controlled humidity [ 66 , 67 , 68 , 69 , 70 , 71 ]. The spin-coating process involves putting a polymer solution on the center of the substrate, which is either spinning at low speed or not spinning at all.…”
Section: Processes Used For Breath-figure Self-assemblymentioning
confidence: 99%
“…Based on the solvent selection guide above, several researches revealed the possibility of using less hazardous solvents such as toluene [87,104,105,106,107,108], and acetone [75,81,86,87,109], THF [43,63,84,87,105,107,108,110,111,112,113,114,115], acetonitrile [116], EA [83,87,109,114,117], and MEK [87] for the BF process (marked in bold in Table 1). Sakurai et al [106] found that by using toluene as the solvent, the mesh size was increased during the lower evaporation rate of kinetic control.…”
Section: Towards a Greener Processmentioning
confidence: 99%
“…In another example, Lakshmi et al [110] fabricated polystyrene–alumina nanocomposite films with ordered arrays, which were prepared from suspensions of amphiphilic-modified alumina particles in polystyrene solutions via the so-called particle-assisted BF process. The key factors for influencing morphological phenomena are particle concentration and the hydrophobic–hydrophilic balance of the amphiphilic-modified alumina particles in the polar or nonpolar solvents (Figure 30).…”
Section: Towards a Greener Processmentioning
confidence: 99%
See 1 more Smart Citation